'Amateur" pros giving country a bad name - Abd Razak, Dzulkifli (2007)
REVELATIONS in recent times of unprofessional conduct and behaviour by professionals and intellectuals have caused embarrassment, not only to the fraternity but the country as well. Those involved are welleducated and are expected to set good examples. To quote the Dalai Lama on his installation as a teaching professor at Emory University, Atlanta, last week; "Education paired with destructive behaviour is wasted." This cannot be more true for those who have intentionally or otherwise, fallen on the wayside.